The exponential twice continuously differentiable $ B$-spline algorithm for Burgers’ equation - Adar, N.; Dag, I.; Ersoy, O. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
The exponential twice continuously differentiable $ B$-spline functions known from the literature as the exponential are usedto set up the collocation method for finding solutions of the Burgers’ equation. The effect of the exponential cubic $ B$-splinesin the collocation method is sought by studying the text problems.